Analisis Kelayakan Usaha Industri Kecil Menengah Tas Di Kecamatan Tanggulangin Kabupaten Sidoarjo - Putri Nadila Nindia Frisca; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Small and medium industries (SMIs) have contributed greatly to national economic growth and community welfare. The important role of the SMI sector can be seen from the employment of 12.39 million people or contributing 66.25% of the total workforce in the industrial sector. The important role of the SME sector can be seen from the absorption of 12.39 million workers or 66.25% of the total workforce in the industrial sector. SMEs are able to contribute to the growth of the non-oil and gas industry by 21.22%. This research uses a qualitative analysis method with primary and secondary data. Data were collected through literature study, observation, interviews and documentation conducted on six informants of bag entrepreneurs in Kedensari Village, Tanggulangin District, Sidoarjo Regency. Business feasibility analysis is determined using the cost and profit analysis formula. The formulas used are R/C ratio analysis, B/C ratio, and ROI. Based on the results of research conducted on six bag entrepreneurs in Kedensari Village, Tanggulangin Subdistrict, Sidoarjo Regency, the analysis of R/C ratio, B/C ratio, ROI shows the results >1 which indicates that the business is feasible. This shows that the value of profits earned by bag entrepreneurs is more than the total costs and business capital incurred during bag production.